2017
DOI: 10.1111/jan.13456
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of non‐pharmacological interventions to reduce the symptoms of mild to moderate anxiety in pregnant women

Abstract: There was insufficient evidence from which to draw overall conclusions regarding the benefit of interventions. Results were predominantly based on small samples. Many papers provided an inadequate description of methods which prevented a full assessment of methodological quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 74 publications
(201 reference statements)
0
49
1
Order By: Relevance
“…Both indicated as well as selective prevention interventions have been proven to be effective in preventing depression [ 53 – 57 ]. However, much is unknown about the effectiveness of preventive interventions on other forms of distress beyond depression, such as anxiety and general stress [ 56 , 58 ]. Furthermore, much less is known about universally applicable interventions that target all pregnant women, without pre-existing symptomatology or risk factors [ 56 , 58 ].…”
Section: Universal Selected and Indicated Prevention Of Parental Dismentioning
confidence: 99%
“…Both indicated as well as selective prevention interventions have been proven to be effective in preventing depression [ 53 – 57 ]. However, much is unknown about the effectiveness of preventive interventions on other forms of distress beyond depression, such as anxiety and general stress [ 56 , 58 ]. Furthermore, much less is known about universally applicable interventions that target all pregnant women, without pre-existing symptomatology or risk factors [ 56 , 58 ].…”
Section: Universal Selected and Indicated Prevention Of Parental Dismentioning
confidence: 99%
“…Descriptive statistics were used to describe pre/post intervention quantitative data from self-report measures using measures of mean and variance including con dence intervals (95% CI) and standard deviation (SD). Qualitative interviews were transcribed prior to conducting template analysis (King 2004) An a priori coding template was developed which was informed by themes identi ed in the literature review (Evans et al 2017(Evans et al , 2019. Transcripts were then read through and new themes which arose were incorporated into the initial template.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological interventions developed speci cally for pregnant women with mental health concerns have demonstrated promising results but have not been rigorously evaluated in large studies (Lavender 2016). Recent systematic reviews found insu cient evidence to draw overall conclusions regarding the bene t of interventions for pregnant women with anxiety (Evans et al 2017(Evans et al , 2019. For this study, the intervention development followed the MRC framework for complex interventions, theoretical and modelling phases (Craig et al 2008).…”
mentioning
confidence: 99%
“…It was considered that the therapeutic intervention components (mind body and cognitive behavioural approaches) could be delivered through supported use of self-help resources. Guided self-help has been reported as an effective intervention for depression and anxiety in general populations (Seekles et al 2011) and has been used as a stand-alone intervention or alongside group interventions for pregnant women with anxiety, stress and depression (Evans et al 2017). Potential self-help resources were identi ed evaluated using IAPT criteria (IAPT 2010) .…”
Section: Additional Considerations and Motivations Informing The Intementioning
confidence: 99%